Form pressure exerted by concrete for a large-scale structure: Its quantification and physicochemical interpretation - Tae Yong Shin; Seongho Han; Jin Hyun Lee; Jae Hong Kim (Case Studies in Construction Materials, 2024)
Securing safety in formwork is one of the most important tasks to be carried out in the initial stage of construction. The form pressure exerted by fresh concrete needs to be identified, and it should be retained by a formwork system. A design pressure is given in literature and standards, but for large structures its precise prediction is required through a detailed analysis or a mock-up test. This study reports the lateral form pressure distribution generated by fresh concrete through a series of mock-up tests. The tests are designed considering the placement for nuclear containment structures; 3.4 m tall and 1.2 m thick concrete wall. The experimental program includes the measurements of setting and temperature of concrete samples in addition to the lateral pressure measurement. The maximum form pressure during layer-by-layer placements depends on the concrete temperature and setting time. These are compared with conventional prediction formulas specified in ACI 347 and DIN 18218. Finally, this paper proposes the simplified prediction formula for maximum form pressure based on concrete temperature.